THE EFFECTIVENESS OF RIVER MORPHOLOGYCAL MODIFICATION TO SOLVE SEDIMENTATION PROBLEM AT SAMPORA WATER TREATMENT PLANT FREE INTAKE - Asep Sulaeman; Galih Habsoro Sundoro (JURNAL TEKNIK HIDRAULIK, 2016)
Sampora Water Treatment Plant (WTP) free intake has been suffering from problems due to sediment and trash deposition at the intake pond that disrupt the water collection process through the intake pump. In this study, several technical approaches were carried out to overcome the related problems such as riverbank cutting, intake length addition, and combination of both approaches. A Physical Hydraulic Model Tests was conducted in order to assess the effectiveness of each approach before it is applied in the field. The Physical Hydraulic Model Tests was performed into four series examinations, there is the existing condition, riverbank cutting at the upstream and downstream of intake, intake length addition, and combination between riverbank cutting and intake length addition. The results showed that riverbank cutting has been directing the river main flow from right to the left side of river with an average flow velocity at in front of intake above 0.70 m/s. The main flow shifting causes the suspended load sediment deposition in front of intake reduced significantly. This condition also causes bed load sediments in front of intake area almost completely scoured. Riverbank cutting chosen as the best approach because the flow pattern is smoother and more streamlines than the other series.